2016
DOI: 10.3390/ijms17060840
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Hydrated Geranylphenols and in Vitro Antifungal Activity against Botrytis cinerea

Abstract: Geranylated hydroquinones and other geranylated compounds isolated from Aplydium species have shown interesting biological activities. This fact has prompted a number of studies where geranylated phenol derivatives have been synthesized in order to assay their bioactivities. In this work, we report the synthesis of a series of new hydrated geranylphenols using two different synthetic approaches and their inhibitory effects on the mycelial growth of Botrytis cinerea. Five new hydrated geranylphenols were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Antifungal activities against B. cinerea of all synthesized compounds were evaluated. On the other hand, the effect of chemical modification of the side chain on antifungal activity has received much less attention, i.e., it has been shown that the hydrated derivative of 2-allylphenol exhibits antifungal activity against P. aphanidermatum, V. mali, B. cinerea and R. cereals [16], whereas some hydrated derivatives of geranylated phenols (Figure 2) inhibit the mycelial growth of B. cinerea [14].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Antifungal activities against B. cinerea of all synthesized compounds were evaluated. On the other hand, the effect of chemical modification of the side chain on antifungal activity has received much less attention, i.e., it has been shown that the hydrated derivative of 2-allylphenol exhibits antifungal activity against P. aphanidermatum, V. mali, B. cinerea and R. cereals [16], whereas some hydrated derivatives of geranylated phenols (Figure 2) inhibit the mycelial growth of B. cinerea [14].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of geranylated phenols is well described and generally it proceeds by direct coupling of geraniol with the proper phenol in the presence of BF3•OEt2 as a catalyst and dioxane as solvent [1,9,14,[17][18][19]. Alternatively, BF3•OEt2/AgNO3 has been used as catalyst and acetonitrile as solvent [11,12].…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Other synthetic geranylphenols, such as 2-geranyl-5methyl resorcinol and 4-geranyl-5-methyl resorcinol ( Figure 1A), showed antimicrobial and antifungal activities [16][17][18][19] . Recently, our research group has developed the synthesis, structural determination and antifungal activity of a series of linear geranylphenols derivatives of 2-geranylhydroquinones, such 2-geranylphloroglucinol ( Figure 1A) [20][21][22][23][24][25][26] .…”
Section: Linearmentioning
confidence: 99%